Energy-efficient neural network design using memristive MAC unit - Yu, Shengqi; Bunnam, Thanasin; Triamlumlerd, Sirichai; Pracha, Manoch; Xia, Fei; Shafik, Rishad; Yakovlev, Alex (Frontiers in Electronics, 2022)
Artifcial intelligence (AI) applications implemented with neural networks (NNs) require extensive arithmetic capabilities through multiply-accumulate (MAC) units. Traditional designs based on voltage-mode circuits feature complex logic chains for such purposes as carry processing. Additionally, as a separate memory block is used (e.g. in a von Neumann architecture), data movements incur on-chip communication bottlenecks. Furthermore, conventional multipliers have both operands encoded in the same physical quantity, which is either low cost to update or low cost to hold, but not both. This may be signifcant for low-energy edge operations. In this paper, we propose and present a mixed-signal MAC unit design with in-memory computing to improve both latency and energy. This design is based on a single-bit multiplication cell consisting of a number of memristors and a single transistor switch (1TxM), arranged in a crossbar structure implementing the long-multiplication algorithm. The key innovation is that one of the operands is encoded in easy to update voltage and the other is encoded in non- volatile memristor conductance. This targets operations such as machine learning which feature asymmetric requirements for operand updates. Ohm’s Law and KCL take care of the multiplication in analog. When implemented as part of a NN, the MAC unit incorporates a current to digital stage to produce multi-bit voltage-mode output. The computation latency consists of memory writing and result encoding operations, with the Ohm’s Law and KCL operations contributing negligible delay. When compared with other memristor-based multipliers, the proposed work shows an order of magnitude of latency improvement in 4-bit implementations because of the Ohm’s Law and KCL time savings and the short writing operations for the frequently updated operand represented by voltages. In addition, the energy consumption per multiplication cycle of the proposed work is shown to improve by 74% to 99% in corner cases. To investigate the usefulness of this MAC design in machine learning applications, its input/ output relationships is characterized using multi-layer perceptrons (MLPs) to classify the hand-writing digit dataset MNIST. This case study implements a quantization-aware training and includes the non-ideal effect of our MAC unit to allow the NN to learn and preserve